Understanding the Relationship between Knowledge and African Americans’ Donation Decision-Making - Jacob Arriola, Kimberly R. (2007)
OBJECTIVES: To explore the association between different types of knowledge related to donation and transplantation and the expression of donation intentions via one’s driver’s license, a donor card, or sharing one’s wishes with family. METHODS: Cross-sectional data were gathered via self-administered questionnaire from 425 Black adults, age 18 years and older who were recruited from nine churches in a large metropolitan area in the southeast United States. RESULTS: Results indicate that knowledge of the allocation system and experiential knowledge of a transplant recipient are associated with donation intentions after controlling for age, gender, and highest level of education. However, the following types of knowledge were unrelated to donation intentions: donation-related statistics (including an understanding of African Americans’ overrepresentation among those in need), the donation process, the process for determining medical suitability, and religious institutions’ support for donation. CONCLUSIONS: Findings suggest that the relationship between donation-related knowledge and donation intentions is complex and may depend on the specific type of knowledge being measured. PRACTICE IMPLICATIONS: Knowledge of the allocation system and experiential knowledge of a recipient may be critical aspects of the donation decision-making process. Research findings suggest the need for an educational approach that seeks to improve the specific types of knowledge that are most strongly associated with donation intentions.